2017
DOI: 10.22373/jppm.v1i1.1728
|View full text |Cite
|
Sign up to set email alerts
|

EFEKTIVITAS PENERAPAN PEMBELAJARAN MATEMATIKA QUR’ANI DALAM PEMBELAJARAN HIMPUNAN

Abstract: Conducting successful mathematics instructions that attach values is a major issue of mathematics education recently. Various programs have been done to meet the purpose. One of them is knowledge islamization which is believed as an alternative-strategic solution. This effort is compatible with the objective of education in Aceh and Indonesia Education System that annunciate the goal of Education in Indonesia to bring the people into religious life. Then, integration of Islamic values onto mathematics instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The Qur'an contains verses about mathematics, even though it is implied (Gradini et al, 2017;Nursupiamin, 2014;Pendra, 2012;Yusufa, 2014). Several verses that contain the concept of monotheism after calculating the "fadic" system are indicated to have a numerical value of one contained in the QS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Qur'an contains verses about mathematics, even though it is implied (Gradini et al, 2017;Nursupiamin, 2014;Pendra, 2012;Yusufa, 2014). Several verses that contain the concept of monotheism after calculating the "fadic" system are indicated to have a numerical value of one contained in the QS.…”
Section: Introductionmentioning
confidence: 99%
“…In its application, students' faith in Allah the Almighty can increase and make students understand the relationship between the Qur'an and mathematics that can be integrated into learning at school. However, a long-standing problem in schools, particularly Islamic schools, is that students who receive mathematics lessons are unaware of this relationship, so how can a student add a religious attitude that should be produced by mathematics lessons (Gradini et al, 2017)?…”
Section: Introductionmentioning
confidence: 99%
“…Ada beberapa peneliti yang juga membuktikan bahwa kemampuan matematika ada kaitannya dengan kemampuan bidang ilmu lainnya, seperti penelitian yang dilakukan oleh Zairi dan kawan-kawan yang menegaskan bahwa peserta didik yang mempunyai kemampuan yang baik dalam bidang matematika mempunyai pengaruh besar terhadap kecepatan menyelesaikan soal fisika (Zairi & Sutrisno, 2017). Gradini dan kawan-kawan juga telah memberikan kesimpulan bahwa matematika Qur'ani memberikan kemudahan bagi peserta didik dalam memahami materi himpunan (Gradini et al, 2017).…”
Section: Pendahuluanunclassified
“…According to (Asdarina & Arwinda, 2020), character education improves both student achievement and attitude. Another study found that Al-Qur'anbased mathematics learning tools are effectively applied to improve students' abilities and character (Gradini et al, 2017). Moreover, it is important to develop teaching materials integrated with Islamic characters to change the perception of mathematics teachers.…”
Section: Introductionmentioning
confidence: 99%